Návrh změn systému odměňování zaměstnanců ve společnosti Sorin s.r.o. - Zlámalíková, Lucie (Vysoké učení technické v Brně. Fakulta podnikatelská, 2019)
Bakalářská práce se zaměřuje na návrh změn v systému odměňování zaměstnanců ve společnosti Sorin s.r.o.. Práce se skládá celkově ze tří částí. V teoretické části jsou zmíněny pojmy související s lidskými zdroji a systémem odměňování. Analytická část zahrnuje analýzu současného stavu společnosti a trhu. V poslední části je řešen návrh na zlepšení systému odměňování a jeho ekonomické zhodnocení.

The bachelor thesis focuses on the proposal of changes in the system of remuneration of employees in the company Sorin s.r.o.. The work consists of a total of three parts. The theoretical part mentions the concepts related to human resources and the remuneration system. The analytical part includes an analysis of the current state of the company and market. In the last part, a proposal to improve the remuneration system and its economic appreciation is dealt with.
Proposal of Changes in the System of Remuneration of Employees in Company Sorin s.r.o.
Keywords: lidské zdroje; zaměstnanec; odměňování; celková odměna; mzda; human resources; employee; remuneration; overal reward; wage